Long-term Consequences of Congenital Adrenal Hyperplasia due to Classic 21-hydroxylase Deficiency in Adolescents and Adults - Kim, Ja Hye.; Choi, Jin-Ho; Kang, Eungu; Kim, Yoon-Myung; Lee, Beom Hee; Yoo, Han-Wook (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background The management of congenital adrenal hyperplasia (CAH) from pediatric to adulthood is challenging to achieve optimal growth and puberty. This study characterizes the clinical outcomes of 21-hydroxylase deficiency.Methods 53 CAH patients were included (33 females, 15 and 18 patients with the salt-wasting [SW] and simple-virilizing [SV] forms; and 20 males, 16 and 4 patients with the SW and SV forms). We reviewed growth parameters, pubertal status, and long-term morbidities.Results In females, the age at pubertal onset and pubarche was 9.6±0.9 and 10.5±1.9 years, respectively, which was significantly earlier in the SV form (p=0.005). In males, the ages at pubertal onset and pubarche were 10.1±2.0 and 10.7±2.5 years, respectively, which were not significantly different between the groups. Forty patients reached adult height: −2.1±1.6 SDS in males and −1.5±1.1 SDS in females. Obesity and overweight was significantly common in adult patients. Testicular adrenal rest tumors were found in 4 SW males. 5 patients had adrenal tumor including adenoma, adenocarcinoma, or myelolipoma.Conclusions Reduced adult height and obesity/overweight are prevalent in adulthood. Adolescents and adults with 21-hydroxylase deficiency should be monitored for long-term consequences.
Keywords: adrenal gland neoplasm; congenital adrenal hyperplasia; testicular adrenal rest tumor; 21-hydroxlyase deficiency